2002
DOI: 10.1021/ja0266058
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Computational Studies on Iron and Manganese Superoxide Dismutases:  Nature of the Chemical Events Associated with Active-Site pKs

Abstract: A combined spectroscopic/computational approach has been utilized to explore the chemical origins of the active-site pKs of the structurally homologous Fe- and Mn-dependent superoxide dismutases (SODs). Absorption, circular dichroism, magnetic circular dichroism, and variable-temperature, variable-field magnetic circular dichroism spectroscopic experiments have permitted us to determine electronic transition energies and polarizations, as well as ground-state spin Hamiltonian parameters. These experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
87
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 56 publications
11
87
0
1
Order By: Relevance
“…Recent magnetic circular dichroism (MCD) spectroscopic and computational studies of Mn-and FeSOD confirmed the importance of these second coordination sphere amino acids as they participate in an extended H-bonding network that affects the protonation state of the axially coordinated solvent (shown in superscript in Eq. (1)) [65,66]. This interaction is essential in tuning the redox potential of the Mn center for each half-reaction with superoxide.…”
Section: Past Studiesmentioning
confidence: 99%
“…Recent magnetic circular dichroism (MCD) spectroscopic and computational studies of Mn-and FeSOD confirmed the importance of these second coordination sphere amino acids as they participate in an extended H-bonding network that affects the protonation state of the axially coordinated solvent (shown in superscript in Eq. (1)) [65,66]. This interaction is essential in tuning the redox potential of the Mn center for each half-reaction with superoxide.…”
Section: Past Studiesmentioning
confidence: 99%
“…Herein, we show that the redox properties of the brominated non-N-alkylated and the N-alkylated Mn(III) ortho-pyridylporphyrins are indeed nearly identical, allowing us to evaluate the electrostatic contribution in the catalysis of O 2 . dismutation.…”
mentioning
confidence: 95%
“…The redox potential of all superoxide dismutases was found to be similar, independently of the type of the metal in the active site. It is around midway (ϩ360 mV versus NHE) 1 (17) between the potential for the oxidation (Ϫ160 mV versus NHE) and for the reduction of O 2 .…”
mentioning
confidence: 99%
See 2 more Smart Citations